2016
DOI: 10.2147/ppa.s94247
|View full text |Cite
|
Sign up to set email alerts
|

Subjects with osteoarthritis can easily use a handheld touch screen electronic device to report medication use: qualitative results from a usability study

Abstract: ObjectivesElectronic data capture is increasingly used to improve collection of patient-reported outcome measures in clinical trials and care. The validation of electronic patient-reported outcome devices requires information on patient preference and ease of use. This study conducted usability testing for a General Symptom Questionnaire and Medication Module™ on a handheld device for subjects with osteoarthritis (OA) to determine whether subjects can report on their symptoms and medication use using an electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Only 15% (5/32) of articles stated that patients were included in the development of the apps. A qualitative phase occurred in only 18% (6/32) of the cases [19,27,30,33,36,37]. This qualitative phase consisted of individual interviews (4 different studies), patient focus group (1 study), or patients focus groups and individual interviews (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…Only 15% (5/32) of articles stated that patients were included in the development of the apps. A qualitative phase occurred in only 18% (6/32) of the cases [19,27,30,33,36,37]. This qualitative phase consisted of individual interviews (4 different studies), patient focus group (1 study), or patients focus groups and individual interviews (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…Previous single method usability studies were limited in their findings. Some studies have assessed usability using only qualitative data [72-74]. These studies can only elucidate an understanding of how and why participants make certain choices when using a prototype or their overall assessment of the utility.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical use of patient e-questionnaires is growing rapidly, 32 there are few prior reports of systematic questionnaire development processes and limited data on patient usability preferences for touch screen questionnaires. 15 Our rapid-cycle design approach enabled us to achieve a summative SUS score of 84.2. This score was well above the reported mean of 68 across web-based systems and corresponds to a subjective usability rating of "excellent" and percentile rank of 95 percent (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study did not demonstrate usability constraints in patients with arthritis, others have also suggested that certain patients prefer a stylus for touch screen questionnaires, and this option should be made available to any user. 15,38 Participants also indicated that functions such as accessing the device keyboard and swiping to advance the screen might not be intuitive to all users ("familiarity with touch screen technology"). Accordingly, we added simple instructions regarding these features on the home screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation